Perceived meaning of life and satisfaction with life: A research synthesis using an online finding archive - Sameer, Yomna; Eid, Yasmine; Veenhoven, Ruut (Frontiers in Psychology, 2023)
Introduction “Meaning” and “happiness” are leading topics in positive psychology, but their relationship is not well understood. The first step to better understanding is to inspect the pattern of correlations found in the research literature. Specifically, we seek answers to the following questions of fact: (1) Is there a correlation between perceived meaning of life and satisfaction with life? (2) If so, is that correlation positive or negative? (3) How strong is this correlation? (4) How variable is this correlation across persons and situations? (5) Do the correlations differ across components of happiness? (6) What aspects of meaning are most/least associated with happiness? (7) What sources of meaning are most/least associated with happiness? (8) Does seeing meaning relate differently to happiness than searching for meaning? Method We took stock of the available research findings, using the World Database of Happiness, which holds standardized descriptions of 171 observed relations between perceived meaning of life and satisfaction with life. Results We found strong correlations between happiness and the degree of perceived meaning in life but little correlation with the pursuit of meaning. While the correlation with the degree of meaning is positive at the micro-level of individuals, it appears to be negative at the macro-level of nations. Discussion Having established the above mentioned matters of fact, we considered the following questions on causality: (1) Is there an innate need for meaning? (2) How does the perceived meaning of life otherwise affect satisfaction with life? (3) How does satisfaction with life affect the perceived the meaning of life? (4) Why is the correlation positive at the micro-level of individuals, but negative at the macro-level of nations? Conclusions We conclude that there is no innate human need for meaning. Still, the perceived meaning of life can affect life satisfaction in various other ways, while life satisfaction will also affect the sense of meaning. Both positive and negative effects can be involved, the balance of which tends to be positive for seeing meaning but close to neutral for pursuing meaning.